2009
DOI: 10.4314/ijhr.v2i3.47905
|View full text |Cite
|
Sign up to set email alerts
|

Phytosomes: The New Technology for Enhancement of Bioavailability of Botanicals and Nutraceuticals

Abstract: and full-text of published articles. The journal is devoted to the promotion of health sciences and related disciplines (including medicine, pharmacy, nursing, biotechnology, cell and molecular biology, and related engineering fields). It seeks particularly (but not exclusively) to encourage multidisciplinary research and collaboration among scientists, the industry and the healthcare professionals. It will also provide an international forum for the communication and evaluation of data, methods and findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 12 publications
(15 reference statements)
0
50
0
1
Order By: Relevance
“…Thereby, nanonisation of plant extracts could be a valuable aid to increase the efficiency of plant extract and minimise their side effects. [17] Scanning electron images of surface morphology of prepared nanosuspension revealed their smooth texture. Their pictures showed that most of the particles were having spherical shape and smooth topology.…”
Section: Particle Size Analysis and Morphological Characterisationmentioning
confidence: 96%
“…Thereby, nanonisation of plant extracts could be a valuable aid to increase the efficiency of plant extract and minimise their side effects. [17] Scanning electron images of surface morphology of prepared nanosuspension revealed their smooth texture. Their pictures showed that most of the particles were having spherical shape and smooth topology.…”
Section: Particle Size Analysis and Morphological Characterisationmentioning
confidence: 96%
“…Due to drugphospholipid complex formation the bioavailability of the active constituent is increased, along with prolonged duration of action. [17] …”
Section: Role Of Phosphatidylcholine In Phytosome Preparationmentioning
confidence: 99%
“…They are cell membrane building blocks, making up the matrix into which fit a large variety of proteins that are enzymes, transport proteins, receptors, and other biological energy converters. In humans and other higher animals the phospholipids are also employed as natural digestive aids and as carriers for both fat-miscible and water miscible nutrients 4 .…”
Section: Disadvantages Of Herbal Medicinesmentioning
confidence: 99%
“…The leaves have also been shown to possess good anti-stress and analgesic activity. 4. Curcuma Longa (Turmeric) 50,51 : Turmeric commonly known as Haldi and has been used for thousands of years as a dye, a flavoring and a medicinal herb.…”
Section: Ginkgoselect Phytosome Vs Ginkgo Biloba Extractmentioning
confidence: 99%